Olfactory dysfunction in type II diabetes: Therapeutic options and lessons learned from other etiologies – A scoping review. Issue 4 (August 2022) - Sivakumar, Ram; White, Jacob; Villwock, Jennifer
Abstract: Introduction: Olfactory dysfunction (OD) is highly prevalent amongst type 2 diabetes mellitus (DM2) patients and has many associated health risks. For example, OD can lead to poor nutrition, safety issues related to diminished hazard detection, and increased mortality rates. While limited research exists about therapeutics for DM2-associated OD, recovery of olfactory function is better studied in other pathologic states. The objectives of this scoping review are to synthesize the existing data on interventions for DM2-associated OD and present the evidence for therapies that have been utilized for non-DM2-associated causes of OD. Additionally, the potential therapeutic opportunities for patients with DM2 are explored. Methods: A scoping review was conducted with a medical librarian to identify studies investigating treatments of DM2-related OD. 6 databases were searched (Embase, CINAHL, the Cochrane Library, Google Scholar, OVID Medline, and Web of Science). Studies were eligible if the primary discussion involved treatment of olfactory deficits in the context of DM2. All publication dates were included, and studies published in languages other than English were excluded. Results: 3631 articles were identified; 3 articles met inclusion criteria and underwent full text review. Hyperbaric oxygen (HBO), the DPP-4 inhibitor Linagliptin and the GLP-1 agonists Exenatide and Liraglutide are the only therapeutics that have been used in the context of DM2. Only HBO and GLP-1 agonists produced statistically significant improvements in olfactory identification. The literature regarding non-DM2-associated OD supports interventions such as olfactory training, dietary supplements, and intranasal insulin. Specifically, olfactory training was very effective in many contexts such as post-viral and traumatic OD while being affordable and non-invasive. Conclusion: This scoping review of olfactory rehabilitation options for DM2-induced OD demonstrates a paucity of prospective investigations of plausible therapeutics. Additionally, treatments for OD related to non-DM2-associated etiologies, such as olfactory training, are well-studied, efficacious, and should be investigated in the context of DM2. Future investigation has the potential to enhance the quality of clinical intervention for OD and improve short- and long-term outcomes for DM2 patients. Highlights: Limited research exists about reversing olfactory dysfunction in type 2 diabetics. Three interventions were identified in the scoping review. Hyperbaric oxygen and GLP-1 agonists showed improvement in smell identification. DPP-4 inhibitors did not produce meaningful improvement in smell identification. Other therapeutics such as olfactory training should be investigated in diabetics.